Critical Realism meets kritische Sozialtheorie: Ontologie, Erklärung und Kritik in den Sozialwissenschaften - Mader, Isabell; Lindner, Urs (transcript, 2017)
Critical Realism, in the form that evolved in the Anglo-Saxon space since the 1970s, not only anticipates many insights of current realism debates, but also elaborates these for the social sciences. Venturing beyond modern nature/culture-dualism, this approach proposes a non-deterministic concept of causality that enables a new understanding of social structures, cultural configurations, and agents, and connects them to an ethics of good life. For the very first time, this volume introduces Critical Realism into the germanophone context, and into a dialogue about local (i.e. German) endeavors for a critical social theory.